Developing the “Language Profile Test” for Greek Students aged 11-15 Years. - Thoma, Ralia (L1-Educational Studies in Language and Literature, 2023)
This paper discusses the development of the “Language Profile Test,” a tool for assessing the underlying component skills of reading fluency and comprehension for students aged 11–15 in the context of Greek as L1. The test consists of five subtests: three reading subtests (isolated words, pseudowords, and text), spelling (single-word spelling), comprehension, and vocabulary (cloze test). The paper aims to present the development of the test, which was based on previous research on lexical representations, specialized corpora, word-frequency lists, and cloze tests as a measure of vocabulary assessment and comprehension, reading fluency, and spelling. Special emphasis has been given to the asymmetry in the transparency of Greek orthography between the feedforward (reading) and feedback (spelling) directions that were considered for the test creation. The “Language Profile Test” was tested on a sample of 346 students. Our findings revealed that students fell into three performance categories for each subtest: high, average, and low. This classification can give teachers more insights into students’ challenges regarding the underlying components of reading fluency and comprehension.